O quartinho: a dependência doméstica na habitação multifamiliar na cidade de João Pessoa(PB) no século XXI - Morais, Fernando de Oliveira (2017)
The research aims to analyze and reveal the contemporary settings of the maid's room, popularly known as "little room", which integrates the worker’s housing and workplace, from the apartment launches ads in the city of João Pessoa in the time span from 2001 to 2015. The maid's room has undergone transformations in the history of Brazilian homes, being considered an indissoluble space of the urban residence, and even representative of the modern remnants of the slaves quarters, according to the authors Reis Filho, Carlos Lemos, Yves Bruand, Chico Veríssimo and William Bittar. Recently, with the achievements of labor rights, with changes in the economy and with the diversification of the way of living, a subject studied by Antônio Cabrita and Douglas Brandão, Brazilian housing has undergone changes in form and use. Such problematic instigated the formulation of questions that led to this research: what and how are the contemporary spatial configurations of the service area in the multifamily residentials of the city of João Pessoa as a socially produced space? The elaborated hypothesis was that this space tends not to perform its original designation as a dormitory for the domestic worker, also presenting reduced dimensions in relation to the ones built in the twentieth century. In order to answer the aforementioned question, the research was based on an analysis of apartment launches ads in newspapers classifieds of the city of João Pessoa, in the aforementioned period, and on construction companies websites, in order to record the highest number of conceptions of the maid's room in residential buildings. Subsequently, the most representative buildings were chosen from among the typologies identified and the elements of analysis: location, access, dimensions and furniture layout. On-site visits to the housing units were made to witness their current uses, using photographic record and the measurement of the space in loco. The study reveals that the supplying of a maid's room is directly related to the owner purchasing power. However, its use has been reduced considerably by the preference for new forms of domestic service without employment and without the worker living in the employer house, the new forms of living, the profile of families and the needs of the use and functions of the domestic space. In relation to the production of this space, it is stated that in the majority of ads collected, the developers and construction companies assign minimal dimensions to the maid’s rooms or even less than the ones advertised, as well as other resources that depreciate the maid’s room in relation to the other rooms of the residence. Thus, the research contributes to the iconographic and architectural record, as well as to the discussion about the evolution of the ways of living in Brazilian society, particularly the medium to high income layers in the city of João Pessoa, and its refusals in residential spaces,also providing subsidies that support the projectual action, bringing a reflection on the transformations of the "little room".